CCR9 interactions support ovarian cancer cell survival and resistance to cisplatin-induced apoptosis in a PI3K-dependent and FAK-independent fashion - Johnson Erica L; Singh Rajesh; Johnson-Holiday Crystal M; Grizzle William E; Partridge Edward E; Lillard James W; Singh Shailesh (BMC, 2010)
Abstract Background Cisplatin is more often used to treat ovarian cancer (OvCa), which provides modest survival advantage primarily due to chemo-resistance and up regulated anti-apoptotic machineries in OvCa cells. Therefore, targeting the mechanisms responsible for cisplatin resistance in OvCa cell may improve therapeutic outcomes. We have shown that ovarian cancer cells express CC chemokine receptor-9 (CCR9). Others have also shown that CCL25, the only natural ligand for CCR9, up regulates anti-apoptotic proteins in immature T lymphocytes. Hence, it is plausible that CCR9-mediated cell signals might be involved in OvCa cell survival and inhibition of cisplatin-induced apoptosis. In this study, we investigated the potential role and molecular mechanisms of CCR9-mediated inhibition of cisplatin-induced apoptosis in OvCa cells. Methods Cell proliferation, vibrant apoptosis, and TUNEL assays were performed with or without cisplatin treatment in presence or absence of CCL25 to determine the role of the CCR9-CCL25 axis in cisplatin resistance. In situ Fast Activated cell-based ELISA (FACE) assays were performed to determine anti-apoptotic signaling molecules responsible for CCL25-CCR9 mediated survival. Results Our results show interactions between CCR9 and CCL25 increased anti-apoptotic signaling cascades in OvCa cells, which rescued cells from cisplatin-induced cell death. Specifically, CCL25-CCR9 interactions mediated Akt, activation as well as GSK-3β and FKHR phosphorylation in a PI3K-dependent and FAK-independent fashion. Conclusions Our results suggest the CCR9-CCL25 axis plays an important role in reducing cisplatin-induced apoptosis of OvCa cells.